Nanometer porous composite diaphragm, preparation method thereof and lithium ion battery

By coating the metal organic frame material layer on the lithium-ion battery separator to form a nanoporous composite separator, the problem of thermal runaway in lithium-ion batteries at high temperatures is solved, and the safety and circulation performance of the battery are significantly improved.

CN119852644APending Publication Date: 2025-04-18WUXI NES ADVANCED MATERIALS & TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311300879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are thermally out of control at high temperatures, resulting in insufficient battery safety, which has become the main obstacle in battery applications.

Method used

A nanoporous composite separator is used, which consists of a base film and a metal organic frame material layer. The metal organic frame material layer is attached to at least one side of the base film, and can effectively adsorb strong oxidative impurities and harmful gases in the battery.

Benefits of technology

The nanoporous composite separator can completely suppress the battery thermal runaway at a high temperature of 250°C, improve the battery's safety performance, and show good cycling performance at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852644A_ABST
    Figure CN119852644A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a nano-porous composite membrane and a preparation method thereof, and a lithium ion battery, the nano-porous composite membrane comprises a base membrane and a metal organic framework material layer, the metal organic framework material layer is attached to at least one side surface of the base membrane, the metal organic framework material layer comprises a metal organic framework material, and the metal organic framework material layer comprises a metal organic framework material. The nano-porous composite diaphragm can resist the high temperature of 250 DEG C. The surface of the polyolefin diaphragm is simply coated with a layer of organic metal framework material, strong oxidation impurities in the battery and harmful strong reducing gas generated by side reaction can be effectively adsorbed, fire and explosion are not detected when the temperature of the diaphragm battery reaches up to 250 DEG C, thermal runaway of the battery can be completely inhibited, and the service life of the battery is prolonged. The safety problem of the battery is solved, and the application field of the battery is widened. In addition, the battery also shows good cycle performance at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the field of battery technology, and in particular to a nanoporous composite diaphragm and a preparation method thereof, and a lithium ion battery. Background Art

[0002] As a key component of power batteries, the primary function of the diaphragm is to ensure battery safety. At present, power batteries generally use microporous films made of polyolefin materials, mainly polyethylene (PE) and polypropylene (PP) diaphragms. However, such diaphragms have poor thermal stability and are prone to size shrinkage when the battery temperature rises (early stage of thermal runaway), resulting in a short circuit in the battery, which is one of the main causes of thermal runaway in the battery.

[0003] The use of polymer separators with excellent thermal stability, such as polyimide, or coating the surface of polyolefin separators with a temperature-resistant layer, such as ceramics, effectively improves the thermal performance of the battery. However, although the thermal performance of the battery is improved, the occurrence of thermal runaway of the battery is not completely suppressed.

[0004] Therefore, how to improve the safety of batteries has become a technical problem that technical personnel in this field need to solve urgently. Summary of the invention

[0005] The technical problem solved by the embodiments of the present invention is how to suppress the occurrence of battery thermal runaway to improve battery safety performance.

[0006] In view of this, an embodiment of the present invention provides a nanoporous composite membrane, comprising a base membrane and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base membrane, the metal organic framework material layer contains a metal organic framework material, and the nanoporous composite membrane can withstand a high temperature of 250°C.

[0007] Optionally, the pore size range of the metal organic framework material is 0.5-5.5 nm.

[0008] Optionally, the thickness of the nanoporous composite membrane is 35-100 μm.

[0009] Optionally, the specific surface area of ​​the metal organic framework material ranges from 700 to 1300 m 2 / g.

[0010] Optionally, the metal organic framework material includes at least one of MOF-801, MIL-101, UiO-66, and MOF-303.

[0011] Optionally, the material of the base film is selected from polyolefin, glass fiber or polyimide.

[0012] Another aspect of the present application provides a method for preparing a nanoporous composite membrane, comprising the following steps:

[0013] (1) mixing a metal organic framework material and a binder in a mass ratio of 10:10 to 19:1 to prepare a slurry;

[0014] (2) The slurry is coated on a base film, and then heated, dried and solidified to obtain the diaphragm.

[0015] Optionally, the thickness of the slurry coated on the base film is in the range of 10 μm to 75 μm.

[0016] Optionally, the binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0017] Optionally, the coating method includes blade coating, gravure roller coating, dip coating, narrow coating or spray coating.

[0018] Optionally, the heating, drying and curing treatment includes: drying in a forced air oven at 60°C-80°C, and then transferring to a vacuum oven and baking at 40°C-70°C for more than 12 hours.

[0019] The present application also provides a lithium-ion battery, comprising the aforementioned nanoporous composite diaphragm, wherein the lithium-ion battery can withstand a high temperature of 250°C.

[0020] Optionally, the capacity retention rate of the lithium-ion battery after 300 cycles is as high as 95%.

[0021] The nanoporous composite membrane provided in the embodiment of the present invention can effectively absorb strong oxidizing impurities in the battery and harmful strong reducing gases produced by side reactions by simply coating a layer of organic metal framework material on the surface of the polyolefin membrane. The battery composed of the nanoporous composite membrane did not detect fire and explosion at a temperature as high as 250°C, which can completely suppress battery thermal runaway, solve battery safety issues, and broaden the application field of the battery. In addition, the battery also shows good cycle performance at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0023] Figure 1A This is a BET test graph of the specific surface area of ​​the metal organic framework material MOF-801 prepared in Example 1 of the present invention;

[0024] Figure 1B It is the pore size distribution test chart of the metal-organic framework material MOF-801 prepared in Example 1 of the present invention;

[0025] Figure 1C It is a photo of the composite separator provided in Example 1 of the present invention;

[0026] Figure 2 It is the comparison chart of the cycle performance of the NMC622|graphite battery in Example 1 and Comparative Example 1;

[0027] Figure 3 It is the cycle performance of the batteries with different proportions of PVDF in the MOF-801 composite separator in Examples 2-4 (the positive electrode is: NMC622, the negative electrode is: graphite), and the charge-discharge voltage range is 2.7-4.2V;

[0028] Figure 4 It is the cycle performance of the batteries with different thicknesses of the MOF-801 nanoporous composite separator in Examples 5-7 (the positive electrode is: NMC622, the negative electrode is: graphite), and the charge-discharge voltage range is 2.7-4.2V;

[0029] Figure 5 It is the thermal performance of the NMC622|graphite battery with the MOF-801 nanoporous composite separator in Example 1 (the positive electrode is: NMC622, the negative electrode is: graphite), the charge-discharge voltage range in the formation stage is 2.7-4.2V, and then charged to 4.3V;

[0030] Figure 6 It is the thermal performance of the NMC622|graphite battery with the commercial PP separator in Comparative Example 1 (the positive electrode is: NMC622, the negative electrode is: graphite), the charge-discharge voltage range in the formation stage is 2.7-4.2V, and then charged to 4.3V;

[0031] Figure 7 It is the thermal performance of the NMC622|graphite battery with the commercial ceramic separator in Comparative Example 2 (the positive electrode is: NMC622, the negative electrode is: graphite), the charge-discharge voltage range in the formation stage is 2.7-4.2V, and then charged to 4.3V. Detailed implementation manners

[0032] As can be seen from the background technology, at present, the safety problems caused by battery thermal runaway are the main obstacles in the application of lithium-ion batteries. The thermal stability of the porous polyolefin separator in the battery is poor, and it is very easy to cause dimensional shrinkage and trigger an internal short circuit in the battery. At present, only using porous membranes with high thermal stability has not been able to completely inhibit the occurrence of battery thermal runaway.

[0033] To solve the above problems, the present application simply coats a layer of organic metal framework material on the surface of the polyolefin diaphragm, which can effectively absorb strong oxidizing impurities in the battery and harmful strong reducing gases produced by side reactions. The diaphragm battery has not been detected to catch fire or explode at a temperature as high as 250°C, which can completely suppress battery thermal runaway, solve battery safety issues, and broaden the application field of the battery. In addition, the battery also shows good cycle performance at room temperature.

[0034] Specifically, an embodiment of the present invention provides a nanoporous composite membrane, comprising a base membrane and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base membrane, the metal organic framework material layer contains a metal organic framework material, and the nanoporous composite membrane can withstand a high temperature of 250°C.

[0035] It should be noted that the nanoporous composite membrane can withstand a high temperature of 250°C, which means that when the nanoporous composite membrane is applied to a lithium-ion battery, the lithium-ion battery can withstand a temperature as high as 250°C without catching fire or exploding.

[0036] It should be noted that the metal organic framework material is attached to at least one side surface of the base film, which means that along the thickness direction of the base film, the metal organic framework material can be attached to one side surface or both sides of the base film.

[0037] The base film is used to carry the metal organic framework material to improve the strength of the nanoporous composite membrane. The material of the base film is selected from at least one of polyolefin, glass fiber or polyimide.

[0038] The metal organic framework material has a porous structure, and the pore size distribution of the metal organic framework material can be fitted by the non-localized density functional method (NL-DFT). In a specific embodiment, the pore size range of the metal organic framework material can be 0.5-5.5nm. The metal organic framework material with this pore size range can effectively adsorb strong oxidizing impurities in the battery, as well as harmful strong reducing gases produced by side reactions, which is beneficial to suppress thermal runaway of the battery and solve the safety problem of the battery.

[0039] In a specific embodiment, the thickness of the nanoporous composite membrane is 35-100 μm, for example, 35 μm, 50 μm, 60 μm, 70 μm, 80 μm, 100 μm.

[0040] It should be noted that the thickness of the nanoporous composite diaphragm of the present application refers to the sum of the thickness of the base film and the thickness of the metal organic framework material layer. The thickness of the metal organic framework material layer cannot be too thick or too thin. If it is too thin, the adsorption effect of impurities is not good. If it is too thick, it will increase the impedance of the battery, thereby affecting the performance of the battery. In a specific embodiment, taking the base film thickness of 25μm as an example, the slurry coating thickness range is 10μm-75μm.

[0041] In a specific embodiment, the specific surface area of ​​the metal organic framework material is in the range of 700 to 1300 m 2 / g. High specific surface area is conducive to the full infiltration of electrolyte. The specific surface area is measured by BET test method under the conditions of 80℃ degassing for 12h and N2 atmosphere at 77K.

[0042] In order to suppress thermal runaway of the battery, a metal organic framework material with a high specific surface area can be selected. In a specific embodiment, the metal organic framework material can be selected from MOF-801. MOF-801 has a suitable pore environment (pore diameter of 0.5-5.5nm) and a high specific surface area. It can effectively adsorb strong oxidizing impurities in the battery and harmful strong reducing gases produced by side reactions, thereby suppressing the occurrence of thermal runaway of the battery and improving battery safety. Of course, in other embodiments, the metal organic framework material can also include at least one of MIL-101, UiO-66, and MOF-303.

[0043] The nanoporous composite membrane provided in the embodiment of the present application can effectively absorb strong oxidizing impurities in the battery and harmful strong reducing gases produced by side reactions by simply coating a layer of organic metal framework material on the surface of the polyolefin membrane. The battery composed of the nanoporous composite membrane did not detect fire and explosion at a temperature as high as 250°C, which can completely suppress battery thermal runaway, solve battery safety issues, and broaden the application field of the battery. In addition, the battery also shows good cycle performance at room temperature.

[0044] To solve the above problems, an embodiment of the present invention provides a method for preparing a nanoporous composite membrane, comprising the following steps:

[0045] Step S1, mixing a metal organic framework material and a binder in a mass ratio of 10:10 to 19:1 to prepare a slurry;

[0046] The adhesive is used to improve the adhesion between the metal frame material and the base film. In a specific embodiment, the adhesive includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0047] In order to ensure the coating effect, the metal organic framework material and the binder are in a mass ratio of 10:10 to 19:1. In a specific embodiment, the mass percentage of the metal organic framework material and the electrolyte gel is 95:5. In other embodiments, the mass percentage of the metal organic framework material and the electrolyte gel can also be 80:20 or 50:50, etc., as long as the mass percentage of the metal organic framework material and the electrolyte gel is within the range of 10:10 to 19:1.

[0048] Step S2, coating the slurry on a base film, and performing a heating, drying and curing treatment to obtain the diaphragm.

[0049] In a specific embodiment, the thickness of the slurry coated on the base film is in the range of 10 μm to 75 μm.

[0050] In a specific embodiment, the coating method includes knife coating, gravure roller coating, dip coating, narrow coating or spray coating.

[0051] In a specific embodiment, the heating, drying and curing treatment includes: drying in a forced air oven at 60°C-80°C, and then transferring to a vacuum oven at 40°C-70°C and baking for more than 12 hours.

[0052] To solve the above problems, an embodiment of the present invention provides a lithium-ion battery, comprising the aforementioned nanoporous composite separator, wherein the lithium-ion battery can withstand a high temperature of 250°C.

[0053] It should be noted that the lithium-ion battery being able to withstand a high temperature of 250°C means that the lithium-ion battery will not catch fire or explode when the temperature reaches 250°C.

[0054] The capacity retention rate of the lithium-ion battery after 100 cycles is as high as 95%.

[0055] The positive electrode material of the battery can be selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, nickel-cobalt-manganese ternary material, and lithium-rich layered material.

[0056] The negative electrode material of the battery can be selected from at least one of graphite, metallic lithium, silicon-carbon, phosphorus-carbon, silicon, and phosphorus.

[0057] The lithium-ion battery provided by the embodiment of the present invention uses the above-mentioned nanoporous composite diaphragm as the battery diaphragm. By simply coating a layer of organic metal framework material on the surface of the polyolefin diaphragm, it can effectively adsorb strong oxidizing impurities in the battery and harmful strong reducing gases generated by side reactions. The battery composed of the nanoporous composite diaphragm has not been detected to catch fire or explode at a temperature as high as 250°C, which can completely suppress the thermal runaway of the battery, solve the safety problem of the battery, and broaden the application field of the battery. In addition, the battery also shows good cycle performance at room temperature.

[0058] The nanoporous composite membrane and its preparation method and the lithium ion battery of the present invention are further described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] Preparation of MOF-801

[0061] Take ZrOCl2·8H2O 28.98g (90mmol), fumaric acid 10.44g (90mmol), formic acid 135mL, DMF 360mL in a 1000mL round-bottom flask; pre-react at 70℃ for 0.5h, then heat to 130℃ and react for 12h; finally wash with tetrahydrofuran for a long time; place the product in a sample bottle and vacuum dry at 130℃ for 12h. The mass of the obtained white product is 22g. Figure 1A and Figure 1B The BET (705m 2 / g) and pore size distribution (0.4–1.5nm) test results.

[0062] Preparation of composite diaphragm

[0063] 1) dissolving PVDF powder in a solvent such as N-methylpyrrolidone (N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide) to obtain a transparent solution (5wt%-10wt%);

[0064] 2) Mixing MOF-801 with the above transparent solution, wherein the mass ratio of MOF-801 to PVDF is 10:10–19:1, and grinding to obtain a white slurry;

[0065] 3) Pour the above slurry onto a commercial polyolefin separator (commercial porous polypropylene membrane with a thickness of 25 μm) and apply it with a scraper. By adjusting the thickness of the scraper, the coating thickness is controlled to be 10 μm-75 μm.

[0066] 4) The film is dried by air blowing at 60-80°C, and then dried under vacuum at 40-70°C for more than 12 hours.

[0067] Figure 1C This is a photo of the prepared MOF-801 nanoporous composite membrane.

[0068] Assembly process of NMC622 and graphite soft pack battery:

[0069] The composite membrane of Example 1 was used as the battery membrane (thickness 35-100 μm), the electrolyte was 1M LiPF6in EC / DMC / EMC (1 / 1 / 1, w / w / w+2wt% VC), and NCM622 was used as the positive electrode (specific capacity: 165 mAh / g, active material loading: 290 g / m 2 ), graphite is the negative electrode (specific capacity: 350mAh / g, active material loading: 151g / m 2 ), assembled into NMC622 and graphite soft pack batteries.

[0070] The capacities of the soft-pack batteries are 0.2Ah and 1.2Ah respectively. The 0.2Ah soft-pack battery is subjected to a cycle performance test, and the 1.2Ah soft-pack battery is subjected to a thermal performance test.

[0071] Cycling performance test of soft pack battery: 1) Formation stage: charge and discharge current: 0.1C, 3 cycles, charge and discharge voltage range: 2.7-4.2V; 2) Cycling stage: charge and discharge voltage range: 2.7-4.2V; charge and discharge current: 0.5C, test results are shown in Figure 2 Thermal performance test of soft pack battery: 1) Formation stage: charge and discharge current: 0.1C, 3 cycles, charge and discharge voltage range: 2.7-4.2V; 2) Then charge the battery to 4.3V, the battery thermal performance test results are shown in Figure 5 .

[0072] Embodiment 2-4

[0073] The mass ratio of MOF-801 and PVDF was replaced with 50:50 (1:1), 80:20 (4:1), and 95:5 (19:1) to prepare nanoporous composite membranes, and then assembled into soft pack batteries to test the cycle performance of the batteries. Please refer to Example 1 for the operation and test steps. The test results are shown in Figure 3 shown.

[0074] Embodiment 5-7

[0075] Composite separators with thicknesses of 35 μm, 50 μm and 100 μm were prepared respectively, and assembled into soft-pack batteries respectively, and the cycle performance of the batteries was tested. Please refer to Example 1 for the operation and test steps. The test results are shown in Figure 4 shown.

[0076] Comparative Example 1

[0077] NCM622 is used as the positive electrode (specific capacity: 165mAh / g, active material loading: 290g / m 2 ), graphite is the negative electrode (specific capacity: 350mAh / g, active material loading: 151g / m 2), electrolyte: 1M LiPF6 / EC-DMC-EMC (1 / 1 / 1, w / w / w+2wt% VC), the diaphragm is a commercial polypropylene diaphragm (PP film) (model: Celgard2500, thickness 25μm), assembled into NMC622 and graphite soft pack batteries.

[0078] Cycle performance test conditions: soft pack battery capacity is 0.2Ah, charge and discharge voltage range: 2.7-4.2V; charge and discharge current: 0.1C, after 3 cycles, cycle test is performed at 0.5C respectively, test results are shown in Figure 2 .

[0079] Battery thermal performance test conditions: soft pack battery capacity is 1.2Ah, charge and discharge voltage range: 2.7-4.2V; charge and discharge current: 0.1C, after 3 cycles, charged to 4.3V, the results are shown in Figure 6 .

[0080] Comparative Example 2

[0081] NCM622 is used as the positive electrode (specific capacity: 165mAh / g, active material loading: 290g / m 2 ), graphite is the negative electrode (specific capacity: 350mAh / g, active material loading: 151g / m 2 ), electrolyte: 1M LiPF6 / EC-DMC-EMC (1 / 1 / 1, w / w / w+2wt% VC), diaphragm selected commercial ceramic diaphragm (18μm), assembled into NMC622 and graphite soft pack batteries.

[0082] Cycle performance test conditions: soft pack battery capacity is 0.2Ah, charge and discharge voltage range: 2.7-4.2V; charge and discharge current: 0.1C, and cycle tests are performed at 0.5C after 3 cycles.

[0083] Battery thermal performance test conditions: soft pack battery capacity is 1.2Ah, charge and discharge voltage range: 2.7-4.2V; charge and discharge current: 0.1C, after 3 cycles, charged to 4.3V, the results are shown in Figure 7 .

[0084] Figure 2 1 is a comparison chart of the cycle performance of NMC622 graphite batteries of Example 1 and Comparative Example 1. Figure 2 As shown, the nanoporous composite membrane prepared in the embodiment of the present application can achieve a circulation effect that is even better than that of the commercial PP membrane.

[0085] Combination Figure 5-Figure 7The nanoporous composite membrane soft-pack battery prepared in the embodiment of the present application did not detect the occurrence of thermal runaway when the temperature was as high as 250°C. The heat resistance of the nanoporous composite membrane is significantly higher than that of commercial PP membranes and commercial ceramic membranes, which significantly improves the safety performance of lithium batteries.

[0086] In summary, the examples of this application verify the cycle performance and thermal performance of the soft-pack battery of the nanoporous composite membrane, and test the cycle performance of nanoporous composite membranes of different thicknesses and different proportions. It can be seen that the battery composed of the nanoporous composite membrane provided in the embodiment of the present invention did not detect fire and explosion at a temperature of up to 250°C, which can completely suppress the thermal runaway of the battery, solve the safety problem of the battery, and broaden the application field of the battery. In addition, the battery also shows good cycle performance at room temperature.

[0087] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

[0089] Although the embodiments of the present invention are disclosed above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A nanoporous composite membrane, characterized in that: It comprises a base film and a metal organic framework material layer, wherein the metal organic framework material layer is attached to at least one side surface of the base film, the metal organic framework material layer comprises a metal organic framework material, and the nanoporous composite membrane can withstand a high temperature of 250°C.

2. The nanoporous composite membrane according to claim 1, wherein the pore size of the metal organic framework material is in the range of 0.5-5.5 nm.

3. The nanoporous composite membrane according to claim 1, characterized in that: The thickness of the nanoporous composite membrane is 35-100 μm.

4. The nanoporous composite membrane according to claim 1, characterized in that: The specific surface area of ​​the metal organic framework material is in the range of 700 to 1300 m 2 / g.

5. The nanoporous composite membrane according to claim 1, characterized in that: The metal organic framework material includes at least one of MOF-801, MIL-101, UiO-66, and MOF-303.

6. The nanoporous composite membrane according to any one of claims 1 to 5, characterized in that: The material of the base film is selected from polyolefin, glass fiber or polyimide.

7. A method for preparing a nanoporous composite membrane according to any one of claims 1 to 6, characterized in that: The steps include: (1) mixing a metal organic framework material and a binder in a mass ratio of 10:10 to 19:1 to prepare a slurry; (2) The slurry is coated on a base film, and then heated, dried and solidified to obtain the diaphragm.

8. The preparation method according to claim 7, characterized in that: The thickness of the slurry coated on the base film is in the range of 10 μm to 75 μm.

9. The preparation method according to claim 7, characterized in that: The binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

10. The preparation method according to claim 7, characterized in that: The coating method includes knife coating, gravure roller coating, dip coating, narrow coating or spray coating.

11. The preparation method according to any one of claims 7 to 10, characterized in that: The heating, drying and curing treatment comprises: drying in a blast oven at 60° C.-80° C., and then transferring to a vacuum oven at 40° C.-70° C. and drying for more than 12 hours.

12. A lithium ion battery, characterized in that: The lithium-ion battery comprises the nanoporous composite separator as described in any one of claims 1 to 6, and can withstand a high temperature of 250°C.

13. The lithium ion battery according to claim 12, characterized in that The capacity retention rate of the lithium-ion battery after 300 cycles is as high as 95%.

Citation Information

Cited By

  • Hydrofluoric acid adsorption diaphragm for lithium iron phosphate battery, preparation method of hydrofluoric acid adsorption diaphragm and battery

    CN121076401A

  • Preparation of MOF-coated polyimide nanofiber and application of MOF-coated polyimide nanofiber in aqueous zinc ion battery negative electrode protective layer

    CN121874967A